Languages and Cultures in Research and Education : Jubilee Volume Presented to Professor Ralf-Peter Ritter on His Seventieth Birthday. - Nagy, laszlo kalman (Jagiellonian University Press, 2011)
This volume is based on the papers presented at the conference entitled "Languages and Cultures in Research and Education", held in Cracow from 19 to 20 May 2009, organized by the Chair of Hungarian Philology of Jagiellonian University on the 20th anniversary of its foundation, as a commemoration of the Year of the Hungarian Language. The conference was dedicated to the celebration of the scientifi c career of Professor Ralf-Peter Ritter on his 70th birthday. In view of the wide range of his scientific interests and the special occasion on which the conference was held, the conference topic.